Studi Literatur Hubungan Ekonomi Indonesia–Belanda: Perdagangan, Investasi, dan Kerja Sama Pembangunan - Aldi Maulana; Samuel Pranata Yoga; Grace Evelina Buji; Rinto Alexandro (Edunomics Journal, 2026)
The economic relationship between Indonesia and the Netherlands has undergone a significant transformation from its colonial legacy toward a more balanced and sustainability-oriented partnership. This study aims to analyze the dynamics of trade, investment, and development cooperation between the two countries and to evaluate their impact on Indonesia’s economic development within the context of globalization. The research employs a systematic qualitative literature review by examining academic publications, policy reports, and statistical data from 2015 to 2025. The findings reveal that bilateral trade has shown consistent growth and diversification, Dutch investment plays an important role in the manufacturing and renewable energy sectors, and development cooperation has shifted toward innovation-based and sustainable partnerships. Overall, Indonesia–Netherlands economic relations are moving toward a strategic, mutually beneficial cooperation that supports Indonesia’s sustainable development agenda.